Small RNAs : their diversity, roles and practical uses - Jockusch, Elizabeth L. (Amsterdam : Elsever, 2012)
This volume is themed on small RNAs and RNAi in insects.
Includes bibliographical references and index.
Keywords: Non-coding RNA; Insects -- Physiology